The Turkish Connection : Global Intellectual Histories of the Late Ottoman Empire and Republican Turkey - Kuru, Deniz; PAPUÇÇULAR, HAZAL (De Gruyter Oldenbourg, 2022)
Covering a rich array of global aspects, ranging from individuals as ideational entrepreneurs to transnational intellectual trajectories, this volume deals with multiple dimensions of global and transnational backgrounds pertaining to Turkey’s intellectual history, starting with the 19th and reaching the 21st-century. The book engages with the late Ottoman and republican Turkish periods through topics such as the transnational processes that contributed to the development of modern Turkish philosophy, the Bosnian and Bulgarian intellectuals at the end times of the Ottoman imperial order, Wilsonianism’s impact, the role of Westerners in promoting Ottoman political agendas, the global connections and ramifi cations of Turkish Islamism as well as Turkish anticlericalism and leftism. The aim is to globalize late Ottoman and republican Turkish intellectual histories by presenting distinct frameworks for advancing the Global Intellectual History agenda in this distinct setting.
Keywords: Global intellectual history; Ottoman intellectual history; Turkish intellectual history; Modern Turkish history